Precise solid-phase synthesis of CoFe@FeOx nanoparticles for efficient polysulfide regulation in lithium/sodium-sulfur batteries - Chen, Yanping; Yao, Yu; Zhao, Wantong; Wang, Lifeng; Li, Haitao; Zhang, Jiangwei; Wang, Baojun; Jia, Yi; Zhang, Riguang; Yu, Yan; Liu, Jian (Nature communications, 2023)
Complex metal nanoparticles distributed uniformly on supports demonstrate distinctive physicochemical properties and thus attract a wide attention for applications. The commonly used wet chemistry methods display limitations to achieve the nanoparticle structure design and uniform dispersion simultaneously. Solid-phase synthesis serves as an interesting strategy which can achieve the fabrication of complex metal nanoparticles on supports. Herein, the solid-phase synthesis strategy is developed to precisely synthesize uniformly distributed CoFe@FeO x core@shell nanoparticles. Fe atoms are preferentially exsolved from CoFe alloy bulk to the surface and then be carburized into a Fe x C shell under thermal syngas atmosphere, subsequently the formed Fe x C shell is passivated by air, obtaining CoFe@FeO x with a CoFe alloy core and a FeO x shell. This strategy is universal for the synthesis of MFe@FeO x (M = Co, Ni, Mn). The CoFe@FeO x exhibits bifunctional effect on regulating polysulfides as the separator coating layer for Li-S and Na-S batteries. This method could be developed into solid-phase synthetic systems to construct well distributed complex metal nanoparticles. Solid-phase synthesis strategy is promising for fabricating desired complex metal nanoparticles on supports. Here, the authors synthesize CoFe@FeOx core-shell nanoparticles as the separator coatings via precise solid-phase method which effectively regulates polysulfides for lithium/ sodium-sulfur batteries.